Electromechanical reliability of a flexible metal-grid transparent electrode prepared by electrohydrodynamic (EHD) jet printing. (October 2016) - Yang, Sang Min; Lee, Yo Seb; Jang, Yonghee; Byun, Doyoung; Choa, Sung-Hoon
Abstract: In this study, we investigated the electrical and mechanical characteristics of an Ag-grid flexible transparent electrode (FTE) as a flexible and even foldable transparent electrode for flexible electronic devices. The Ag-grid FTE was fabricated on a polyethylene terephthalate substrate using the electrohydrodynamic (EHD) jet printing process. We achieved a fine pattern of a line width of 4.6 μm. The Ag-grid FTE exhibited the sheet resistances of ~ 4 Ω/sq. and optical transmittance of around 80% with a pitch of 150 μm. We also used the carbon treated black metal-nanoparticles to lower the haze up to 1%. The effects of the sintering temperature on the microstructure and sheet resistance were investigated. From the sintering temperature of 150 °C, a stable necking between nano-particles began to form, and the sheet resistance substantially decreased. The mechanical flexibility and durability of the Ag-grid FTEs were investigated via bending, stretching, dynamic/static fatigue tests, and adhesion tests. The outward bending test results showed that the Ag-grid FTE can be bent up to 3 mm without failure of the electrode. The stretching test indicated that the Ag-grid FTEs can be stretched to a tensile strain of 9%; however, the Ag-grid was slightly vulnerable at the extreme bending radius in the bending cyclic fatigue tests due to severe strain accumulation. The Ag-grid FTEs exhibited a very stable static bending fatigue property during the 1000 h test as well as an excellent adhesion property. These results indicate that the Ag-grid FTE is a promising electrode scheme for bendable or foldable electronic devices. Highlights: We fabricated a flexible transparent electrode (FTE) electrohydrodynamic printing. We achieved a fine pattern of 4.6 μm with 1% haze. Ag-grid FTE has a superior electrical and optical properties with flexibility. Ag-grid FTE is a promising electrode for bendable or foldable electronic devices.